Transcriptional signature in microglia isolated from an Alzheimer's disease mouse model treated with scanning ultrasound - Gerhard Leinenga; Liviu‐Gabriel Bodea; Jan Schröder; Giuzhi Sun; Yichen Zhou; Jae Song; Alexandra Grubman; Jose M. Polo; Jürgen Götz (Bioengineering & Translational Medicine)
Abstract Transcranial scanning ultrasound combined with intravenously injected microbubbles (SUS+MB) has been shown to transiently open the blood–brain barrier and reduce the amyloid‐β (Aβ) pathology in the APP23 mouse model of Alzheimer's disease (AD). This has been accomplished through the activation of microglial cells; however, their response to the SUS treatment is incompletely understood. Here, wild‐type (WT) and APP23 mice were subjected to SUS+MB, using nonsonicated mice as sham controls. After 48 h, the APP23 mice were injected with methoxy‐XO4 to label Aβ aggregates, followed by microglial isolation into XO4+ and XO4− populations using flow cytometry. Both XO4+ and XO4− cells were subjected to RNA sequencing and transcriptome profiling. The analysis of the microglial cells revealed a clear segregation depending on genotype (AD model vs. WT mice) and Aβ internalization (XO4+ vs. XO4− microglia), but interestingly, no differences were found between SUS+MB and sham in WT mice. Differential gene expression analysis in APP23 mice detected 278 genes that were significantly changed by SUS+MB in the XO4+ cells (248 up/30 down) and 242 in XO− cells (225 up/17 down). Pathway analysis highlighted differential expression of genes related to the phagosome pathway and marked upregulation of cell cycle‐related transcripts in XO4+ and XO4‐ microglia isolated from SUS+MB‐treated APP23 mice. Together, this highlights the complexity of the microglial response to transcranial ultrasound, with potential applications for the treatment of AD.